Myofunctional Therapy for the Treatment of Obstructive Sleep Apnea: Systematic Review and Meta-Analysis - Ferreira, Lucas Gabriel dos Anjos; Miranda, Vanessa Souza Gigoski de; Baseggio, Maria Eduarda Pedroso; Marcolino, Miriam Allein Zago; Vidor, Deisi Cristina Gollo Marques (International Archives of Otorhinolaryngology, 2025)
Introduction Given the severity with which obstructive sleep apnea (OSA) syndrome can affect the patient's health, many therapies have been presented to minimize the occurrence of episodes of airway obstruction during sleep. Regarding non-invasive and effective methods, orofacial myofunctional therapy (OMT) is an important adjuvant in the clinical treatment.Objective To verify the effectiveness of OMT in the treatment of adult patients affected by OSA.Data Synthesis A search strategy was developed with terms adapted to the requirements of the main databases in the health field (PubMed, Cochrane, Embase and secondary databases) to designate the adult OSA population and the OMT intervention. The analysis of the records found was performed by two independent examiners and, at the end, we included five randomized clinical trials that presented the outcome of effectiveness of the OMT verified through the apnea-hypopnea index (AHI).Conclusion The effectiveness of the OMT in the treatment of adult OSA patients was verified, both alone and in association with other interventions, through the reduction in the AHI and the Epworth Sleepiness Scale.
Keywords: myofunctional therapy; sleep apnea; obstructive sleep apnea; syndromes; exercise therapy